1998
DOI: 10.1007/bf03401731
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility Locus for IgA Deficiency and Common Variable Immunodeficiency in the HLA-DR3, -B8, -A1 Haplotypes

Abstract: Crossover events within the MHC indicated a susceptibility locus for IgAD/CVID between the class III markers D821/D823 and HLA-B8, a region populated by 21 genes that include tumor necrosis factor alpha and lymphotoxins alpha and beta. Inheritance of at least this fragment of haplotype 1 appears to be necessary for the development of IgAD/CVID in this family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
93
2
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(102 citation statements)
references
References 64 publications
5
93
2
2
Order By: Relevance
“…It has been estimated that ϳ70% of the human haplotypes are conserved, extended haplotypes or recombinants of no more than two of them (17,32,33). It is generally accepted that a small number of these MHC conserved haplotypes are found in the majority of IgAD patients (5,7,8,10,11,13,19) and that these haplotypes share a susceptibility locus designated IGAD1. To track down this MHC susceptibility locus, most studies have either focused on the B8-DR3 haplotype (13,14) or looked for a shared feature between different haplotypes associated with the disease (8, 10 -12, 15, 18, 19).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been estimated that ϳ70% of the human haplotypes are conserved, extended haplotypes or recombinants of no more than two of them (17,32,33). It is generally accepted that a small number of these MHC conserved haplotypes are found in the majority of IgAD patients (5,7,8,10,11,13,19) and that these haplotypes share a susceptibility locus designated IGAD1. To track down this MHC susceptibility locus, most studies have either focused on the B8-DR3 haplotype (13,14) or looked for a shared feature between different haplotypes associated with the disease (8, 10 -12, 15, 18, 19).…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that a small number of these MHC conserved haplotypes are found in the majority of IgAD patients (5,7,8,10,11,13,19) and that these haplotypes share a susceptibility locus designated IGAD1. To track down this MHC susceptibility locus, most studies have either focused on the B8-DR3 haplotype (13,14) or looked for a shared feature between different haplotypes associated with the disease (8, 10 -12, 15, 18, 19). Conclusions from different groups map the susceptibility locus either to the telomeric class III region (8,(11)(12)(13)15) or to the telomeric class II region (10,18,19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,7 No primary genetic factor has been identified and variation in familial inheritance patterns suggests that IgAD may be due to multiple genetic defects. Several studies have shown association of HLA alleles with IgAD, [8][9][10][11] and the extended haplotype HLA-A1-B8-DR3 occurs more frequently in individuals with IgAD than it does in the general population. This haplotype is known as an autoimmunity risk haplotype as it is associated with several autoimmune pathologies.…”
Section: Introductionmentioning
confidence: 99%